Clinical Diagnosis of Placenta Accreta and Clinicopathological Outcomes - Rosenbloom, Joshua I.; Hirshberg, Jonathan S.; Stout, Molly J.; Cahill, Alison G.; Macones, George A.; Tuuli, Methodius G. (American Journal of Perinatology, 2019)
Objective To investigate the association between the intraoperative diagnosis of placenta accreta at the time of cesarean hysterectomy and pathological diagnosis.Study Design This is a retrospective cohort study of all patients undergoing cesarean hysterectomy for suspected placenta accreta from 2000 to 2016 at Barnes-Jewish Hospital. The primary outcome was the presence of invasive placentation on the pathology report. We estimated predictive characteristics of clinical diagnosis of placenta accreta using pathological diagnosis as the correct diagnosis.Results There were 50 cesarean hysterectomies performed for suspected abnormal placentation from 2000 to 2016. Of these, 34 (68%) had a diagnosis of accreta preoperatively and 16 (32%) were diagnosed intraoperatively at the time of cesarean delivery. Two patients had no pathological evidence of invasion, corresponding to a false-positive rate of 4% (95% confidence interval [CI]: 0.5%, 13.8%) and a positive predictive value of 96% (95% CI: 86.3%, 99.5%). There were no differences in complications among patients diagnosed intraoperatively compared with those diagnosed preoperatively.Conclusion Most patients undergoing cesarean hysterectomy for placenta accreta do have this diagnosis confirmed on pathology. However, since the diagnosis of placenta accreta was made intraoperatively in nearly a third of cesarean hysterectomies, intraoperative vigilance is required as the need for cesarean hysterectomy may not be anticipated preoperatively.
Keywords: placenta accreta; cesarean hysterectomy; clinicopathological outcomes; clinical diagnosis